THE AUTHORITY OF HADITH IN CONTEMPORARY DISCOURSE: REREADING THE VIEWS OF ORIENTALISTS, OCCIDENTALISTS, AND MODERN SCHOLARS - Fahmi Andaluzi; Devi Ganis Prameswari (UNIVERSUM: Jurnal Keislaman dan Kebudayaan, 2025)
Hadith constitutes an authoritative source of Islamic law after the Qur’an. However, throughout its history, its authority has been subject to continuous re-examination, both through isnād (chain of transmission) and matn (content) criticism. This article examines contemporary discourses on ḥadīth criticism and their implications for the authority of hadith by tracing classical and modern literature and comparing them with the views of contemporary Muslim hadith scholars. The findings reveal that contemporary hadith discourse can be mapped into three major perspectives: Orientalists, Occidentalists, and contemporary Muslim scholars. Orientalists such as Goldziher, Schacht, Juynboll, and others, who predominantly employed historical criticism as their main analytical tool, tend to regard hadith as a later socio-political construct, thereby casting doubt on its authority to a significant extent. Their critiques have influenced certain Occidentalist figures who highlight methodological weaknesses within the hadith tradition, particularly in transmission, codification, and the subjective nature of isnād evaluation, with a stronger emphasis on matn criticism. While the critiques of Orientalists and their resonance among modern Muslim thinkers reflect a concern that has encouraged more rigorous and comprehensive engagement with hadith studies among contemporary scholars, they often remain reductive and ahistorical. In response, contemporary hadith scholars such as Nūr al-Dīn ʻItr, al-Idlibī, al-Sibāʿī, and al-Jawābī assert that both isnād and matn criticism had in fact been practiced since the early period, even though methodological frameworks were conceptually systematized at a later stage. Consequently, the substantive authority of hadith as a normative Islamic text remains intact. This article underscores the relevance and urgency of hadith criticism methodologies in addressing modern challenges while reaffirming the central position of hadith within Islamic authority.